Tools for organisation and time management in your research. - García Gámez, María (My University, 2023)
At first glance, time management is an easy task, yet on many occasions we all fail to manage time effectively and make the most of it. As PhD candidates ourselves, we have tried -and failed- to control the amount of time we spend reading, writing, thinking, or even doing absolutely nothing at all! This is why María García has prepared the talk “Tools for organisation and time management in your research”, where she will share her experience in terms of time management and organisation in the hope of helping fellow PhD candidates who might be struggling to meet deadlines while keeping a sound mind and body. She will explain how to use some useful tools such as Zotero in order to make the most of your time while researching, and she will give you some tips to improve your work-life balance.
Keywords: Investigación - Metodología; Organisation; Time management; Research